Associations of Non-suicidal Self-Injury and Psychological Symptoms With Suicide Attempt in Adolescents: Are There Any Gender Differences? - Xu, Huiqiong; Wang, Rui; Li, Ruoyu; Jin, Zhengge; Wan, Yuhui; Tao, Fangbiao (Frontiers in Psychiatry, 2022)
Abstract Background Psychological symptoms and non-suicidal self-injury (NSSI) are independently associated with suicide attempts (SA). Yet, no study has tested the interaction effects between NSSI and psychological symptoms on SA in community adolescent populations, or examined whether the interaction varies by gender. We sought to examine the interaction effects of NSSI and psychological symptoms on SA in adolescents and explore gender differences. Methods A school-based health survey in 3 provinces in China was conducted between 2013-2014. 14,820 students aged 10-20 years completed standard questionnaires, to record the details of various psychological symptoms, SA and NSSI. Results Psychological symptoms and NSSI were independently associated with a higher likelihood of SA in both boys and girls (p<0.001). Adolescents with psychological, conduct or social adaptation symptoms without concurrent NSSI, were twice as likely to report SA (corresponding RORs were 1.80, 1.80 and 2.16, respectively; p<0.01) than those who reported NSSI. Male adolescents with psychological, emotional, conduct or social adaptation symptoms had a higher risk of SA in the non-NSSI group than the NSSI group (corresponding RORs were 2.85, 2.26, 2.30 and 3.01 respectively; p<0.01). While in girls, only adolescents with social adaptation symptoms had a higher risk of SA in the non-NSSI group than NSSI group (corresponding RORs was 1.71, p<0.05). In the non-NSSI group, boys reporting psychological symptoms exhibited a higher likelihood of a SA than their female counterparts. Conclusion Psychological symptoms and NSSI are independently associated with an increased risk of SA in adolescents. However, to some extent, NSSI may reduce the risk of SA among individuals with psychological symptoms, especially in boys.